Investigating impact: Exploring the effect of ‘open’ support on student success - Jennie Rose Steres Blake (Association for Learning Development in Higher Education (ALDinHE), 2019)
Traditional investigations into the impact of skills support on student success tend to focus on embedded or curriculum linked modes of delivery. The subject of this investigation concerns a study of the impact of ‘open’ support delivered through the University of Manchester library’s My Learning Essentials skills programme (MLE). MLE is a blended service providing both face-to-face and online support through two dominant pathways: one which is embedded in the curriculum and one which is ‘open to all’ regardless of degree programme or level of study. The ‘open’ nature of this type of support and the variety amongst the student population who engage with it means that measuring the impact on areas such as attainment has always been difficult. This article will present the results of a small study that investigated a specific cohort of undergraduate students in order to assess whether connections could be drawn between attendance at MLE ‘open’ workshops and degree classification. Although the cohort investigated was quite small, there is evidence of significant positive impact on student attainment as a result of engagement with the MLE programme. The data was run through a regression analysis that controlled for factors that could influence attainment and compared attendees of MLE open workshops with those who did not attend. Beyond the results of the regression analysis the study reveals interesting data around student uptake of MLE as a service and presents the methodology used, the results gained, and the lessons learned throughout the process.